2006
DOI: 10.1073/pnas.0600994103
|View full text |Cite
|
Sign up to set email alerts
|

The Wilms tumor gene, Wt1 , is required for Sox9 expression and maintenance of tubular architecture in the developing testis

Abstract: Mutation of the transcription factor and tumor suppressor gene WT1 results in a range of genitourinary anomalies in humans, including 46,XY gonadal dysgenesis, indicating that WT1 plays a critical role in sex determination. However, because knockout of Wt1 in mice results in apoptosis of the genital ridge, it is unknown whether WT1 is required for testis development after the initial steps of sex determination. To address this question, we generated a mouse strain carrying a Wt1 conditional knockout allele and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
200
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(218 citation statements)
references
References 41 publications
16
200
1
1
Order By: Relevance
“…The following antibodies were used: CD31 (1:250, clone MEC13.3; BD PharMingen, San Diego, CA), FOXL2 (1:500; gift from Marc Fellous, Cochin Institute, Paris, France), FGFR2 (1:500, C17, sc-122; Santa Cruz Biotechnology, Santa Cruz, CA), and AMH (1:200, C20, sc-6886; Santa Cruz Biotechnology). All antibodies used in this work have been validated and used in previous published reports (15,(46)(47)(48)(49). Images were obtained by using a Zeiss (Thornwood, NY) LSM 510 confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The following antibodies were used: CD31 (1:250, clone MEC13.3; BD PharMingen, San Diego, CA), FOXL2 (1:500; gift from Marc Fellous, Cochin Institute, Paris, France), FGFR2 (1:500, C17, sc-122; Santa Cruz Biotechnology, Santa Cruz, CA), and AMH (1:200, C20, sc-6886; Santa Cruz Biotechnology). All antibodies used in this work have been validated and used in previous published reports (15,(46)(47)(48)(49). Images were obtained by using a Zeiss (Thornwood, NY) LSM 510 confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting WT1(ϪKTS) target gene is SOX9, although this gene was not characterized beyond qRT-PCR analysis due to its low level of induction. Recently, using a conditional WT1 knock-out approach, Gao et al (66) demonstrated that ablation of Wt1 expression in Sertoli cells led to a concomitant loss of Sox9 expression, suggesting that WT1 either directly or indirectly regulates Sox9 expression. Our study supports this in vivo observation and further suggests that WT1 may play a direct role in regulating SOX9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…WT1 expression persists in Sertoli cells after gonad formation, but until recently, its functional role in this context was not known, as Wt1-mutant mice die early during embryogenesis. The role of WT1 in Sertoli cells after the bipotential gonad stage was recently addressed by two studies (Gao et al 2006;Rao et al 2006). Gao et al (2006) used a conditional knockout approach to disrupt the Wt1 gene in foetal Sertoli cells at approximately e14.5 and found that this severely disrupted testis cord formation in male embryos and subsequently led to the formation of abnormal tubular architecture and reduced testes size in adult males.…”
Section: Dna-binding Proteins That Regulate Spermatogenesismentioning
confidence: 99%